Angliederung Eupen/Malmedy an Belgien. Das Schicksal der ehemals preußischen Kreise vor 100 Jahren - Klauser, Klaus-Dieter (Jahrbuch des Kreises Euskirchen, 2022)
Keywords: Annexion; Staatsgrenze

Die Bedingungsklausel für Eupen-Malmedy im Versailler Vertrag - Jousten, Wilfried (Zwischen Venn und Schneifel, 2021)
Keywords: Annexion; Eupen-Malmedy; Staatsgrenze; Versailler Vertrag (1919)

Overlapping borders. Images of East Belgium as a transcultural area in contemporary East Belgian literature - Beck, Philippe; Penné, Lesley (Oxford German Studies, 2019)
„In this contribution, we discuss how the East Belgian authors Hannes Anderer, Freddy Derwahl and Leo Wintgens represent history, borders and multilingualism in their novels. These contemporary authors have understood that coming to terms with the past is an important aspect in developing a genuine East Belgian collective identity. Furthermore, the multiple borders (with Germany, the Netherlands and Luxembourg) and the co-existence of several languages in this region have become constitutive of collective self-understanding, also with regard to the construction of a region-specific cultural memory. Finally, we show the narrative strategies used in the novels Unterwegs zu Melusine (2006), Bosch in Belgien (2006) and Wege aus Sümpfen. Roman einer Grenzlandschaft Teil I (2001) and Teil II (2006) in order to bring to bear the relation between minority and majority culture by recurring to imagology.“
Keywords: Annexion; Geschichtsbild; Geschichtsschreibung; Kulturelle Identität; Mehrsprachigkeit; Schriftsteller; Staatsgrenze

"New Belgians" living in an ancient Belgian soil? The annexation and integration of the East Cantons - Brüll, Christoph (Beyond the Great War. Belgium 1918–1928, 2018)
Keywords: Annexion; Staatsgrenze; Versailler Vertrag (1919)

La restauration des forêts belges après la Première Guerre mondiale et le rôle décisif de l’administration forestière dans le cadre de l’annexion des cantons d’Eupen-Malmedy - Tallier, Pierre-Alain (Art&Fact, 2018)
Keywords: Annexion; Aufforstung; Forst; Staatsgrenze; Wald

Pierre Nothomb, het comité de politique nationale en de Belgische annexionistische campagne tijdens en na de Eerste Wereldoorlog - Waele, Maria de (Studies over De Sociaaleconomische Geschiedenis Van Limburg/Jaarboek Van Het Sociaal Historisch Centrum Voor Limburg, 2015)
Keywords: Annexion; Erster Weltkrieg; Nothomb; Pierre (1887–1966); Versailler Vertrag (1919)

"Left to Their Own Devices". Belgium's Ambigious Assimilation of Eupen-Malmedy (1919–1940) - O'Connell, Vincent (Revue Belge d’Histoire Contemporaine, 2013)
„The inter-war period in Eupen-Malmedy remains a sensitive arena in which the experiences and sensibilities of its inhabitants have barely been broached by historians. The controversial milestones of the interwar period in Eupen-Malmedy have been covered over with the palimpsest of what the late Tony Judt has referred to elsewhere as ‘selective forgetting’ where communities as well as individuals shield certain episodes or events of the past from intrusion by historians1. The German historian Freddy Cremer describes this phenomenon as akin to ‘amnesia as therapy’. The period following the Nazi invasion and annexation of the former Germany districts in 1940 and their later liberation conspired to further compound an already complex situation. Since then the historical narrative has been shrouded beneath a veil of silence. This article aims in some small way to pull back this veil so that in Cremer’s words “the past may not be left untouched”.“
Keywords: Annexion; Eupen-Malmedy; Staatsgrenze; Versailler Vertrag (1919)

Belgien und die Ostkantone im Versailler Vertrag. Irredenta-Gebiet, militärische Pufferzone oder Trostpreis? - Balace, Francis (Zoom 1920–2010. Nachbarschaften neun Jahrzehnte nach Versailles, 2012)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage2/2018/03/07/file_36/7584537.pdf
Keywords: Annexion; Eupen; Malmedy; Ostbelgien; Staatsgrenze; Versailler Vertrag (1919)

Das Grenzland von Nordrhein-Westfalen, die Traktatländereien und die niederländischen Grenzkorrekturen 1949 bis 1963 - Woelk, Wolfgang (Zentrum für Niederlande-Studien, Jahrbuch, 1994)
Keywords: Annexion; Auftragsverwaltung; Grenzkonflikt; Nordrhein-Westfalen

Querelles d’Allemands entre Locarnistes. La Question d’Eupen-Malmédy - Poulain, Marc (Revue historique, 1977)
Keywords: Annexion; Eupen-Malmedy; Versailler Vertrag (1919)

Deutsche Annexionspolitik im Westen. Die Wiedereingliederung Eupen-Malmedys im 2. Weltkrieg - Schärer, Martin R. (Lang, 1975)
Keywords: Annexion; Eupen; Malmedy; Ostbelgien; Zweiter Weltkrieg

La Nationalité des Habitants des Cercles d’Eupen et de Malmédy d’Après le Traité de Paix de Versailles - Nisot, Joseph (Journal du Droit International, 1921)
Keywords: Annexion; Eupen-Malmedy; Staatsangehörigkeitsrecht; Staatsgrenze; Versailler Vertrag (1919)